Algorithms for sheet metal nesting. - Herrmann, J.W (IEEE Transactions on robotics and automation)
This paper discusses the problem of minimizing the cost of sheet metal punching when nesting (batching) orders. Although the problem is NP-complete, the solution to a linear programming relaxation yields an efficient heuristic. This paper analyzes the heuristic's worst-case performance and discusses experimental results that demonstrate its ability to find good solutions across a range of cost parameters and problem sizes